Accessible Type 2 diabetes medication through stable expression of Exendin-4 in Saccharomyces cerevisiae - Balius, Gia; Imani, Kiana; Petroff, Zoë; Beer, Elizabeth; Feitosa, Thiago Brasileiro; Mccall, Nathan; Paule, Lauren; Peng, Neo Yixuan; Shen, Joanne; Singh, Vidhata; Strand, Cambell; Zau, Jonathan; et al. (Frontiers in Systems Biology, 2024)
Diabetes Mellitus affects roughly one in ten people globally and is the world's ninth leading cause of death. However, a significant portion of chronic complications that contribute to mortality can be prevented with proper treatment and medication. Glucagon-like peptide 1 receptor agonists, such as Exendin-4, are one of the leading classes of Type 2 Diabetes treatments but are prohibitively expensive. In this study, experimental models for recombinant Exendin-4 protein production were designed in both Escherichia coli and Saccharomyces cerevisiae. Protein expression in the chromosomally integrated Saccharomyces cerevisiae strain was observed at the expected size of Exendin-4 and confirmed by immunoassay. This provides a foundation for the use of this GRAS organism as an affordable treatment for Type 2 diabetes that can be propagated, prepared, and distributed locally.